An Explorative Study on Investigating the Root Causes of Unemployment and Underemployment in a Rural Settlement - Ahmad, Naseer (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper examines the problems of unemployment and underemployment in Pachdaura Kalan Gram Panchayat in Bareilly District. about 10 years ago (2013), most residents of the Panchayat were engaged in seasonal and low-skilled work such as farming, truck driving, daily wage labor and house shuttering. Due to lack of information about employment opportunities and adequate skills, most people were unemployed or engaged in work that did not utilize their full potential. Education levels were also low, which slowed down the development of the Panchayat. Some positive changes have been observed in the Panchayat since 2013. Education levels have improved, and some people are now employed in the government and private sectors. However, most people are still unemployed or in underemployment. For example, people engaged in jobs such as tailoring, truck driving, house shuttering and AC repair are not able to take full advantage of their abilities. Government schemes, such as PM Kisan Samman Nidhi, MNREGA, PM Awas Yojana, Tubewell Subsidy and Ayushman Card, are providing economic and social support to the residents of the Panchayat. These schemes have improved the basic living standards, but it is not enough to reduce unemployment and underemployment. For this, special attention needs to be given to employment-based skill training and education in the Panchayat. This research emphasizes that through skill development and education, can be provided employment to the residents of the Panchayat. This will not only reduce unemployment, but the Rural development will also be rapid.